INDIVIDUAL LEARNING PATHWAYS IN GERMAN LANGUAGE TEACHING: DIFFERENTIATION AND PERSONALIZATION (PALIMPSEST / ПАЛИМПСЕСТ, 2026)
In an increasingly diversified educational landscape, differentiation and personalization in teaching are gaining growing importance. This paper examines how individual learning pathways in German language instruction can be designed and supported to meet the diverse needs and abilities of learners. Based on current didactic concepts and empirical studies, it presents methods and strategies that enable teachers to provide differentiated and personalized instruction. The empirical investigation is based on the results of a questionnaire conducted with students aged 15 to 18 at public schools in various Albanian cities. The aim of the survey was to gain insights into learners’ perceptions, experiences, and challenges related to differentiation and personalization in German language teaching. The results show that students often report limited opportunities to practice German outside the classroom and insufficient learning resources tailored to their individual needs. They also point to difficulties arising from large class sizes and limited digital infrastructure. By analyzing these findings, the study provides a comprehensive overview of the current situation of German as a Foreign Language (DaF) teaching in Albania, while also offering starting points and recommendations for improving teaching and learning processes.
Keywords: differentiation; personalization; digital media; motivation.